A Composite Renal Tumor with Dual Differentiation, Chromophobe and Collecting Duct Carcinoma. (30th August 2018) - Pearson, Lauren; Taatjes, Douglas J.; von Turkovich, Michele; King, Benjamin J.; Zenali, Maryam
Abstract : Chromophobe carcinoma constitutes a small subset of all renal carcinomas. Within this category, rare tumors with divergent differentiation have been recognized. Herein, we report a rare case of composite chromophobe and collecting duct carcinoma and describe its pathologic and clinical features.